Optimization of cone lifter components in C2L Machine for highway concession operation using TRIZ method - Salim, Mohd Azli; Ismail, Azilah; Mohd. Yusof, Sitinor Wardatulaina; Md. Saad, Adzni; Chew, Kit Wayne (UTHM Publisher, 2024)
This study aims to enhance cone laying and picking (C2L) machines used in highway concession operations through the application of TRIZ methodology. The study identified engineering contradictions within the C2L machine and proposed solutions to address them systematically. TRIZ tools were utilized to identify areas for improvement in the assembly and disassembly processes of cone lifters, leading to the redesign and fabrication of C2L machines. Testing of C2L machines demonstrated the effectiveness of the new design in handling cone lifters. Results showed that by increasing the weight capacity and gripping force of the cone lifter improved lifting efficiency and reduced cone slippage. However, it also introduced challenges such as stress on structural components and potential cone deformation. Through the TRIZ methodology, these contradictions were addressed, leading to a redesigned cone lifter with improved durability and performance. TRIZ tools, including the Function Analysis Model, were employed to attribute functions to each component of the C2L system. Additionally, a framework for assessing C2L machine effectiveness in highway concession operations was proposed. The redesign and fabrication of C2L machines, along with various tests demonstrated the success of the new design in handling cone lifters. The findings highlight the importance of TRIZ methodology as a valuable tool for resolving technical contradictions and optimizing C2L machine designs, contributing to a more efficient and sustainable future in transportation infrastructure management.